Maximization of power capture in wind turbines using robust estimation and Lyapunov extremum seeking control - Hawkins, Tony (Greg Anthony) (Kansas State University, 2010)
In recent years, the concern has risen to establish clean sources for electric power generation. In 2009, Kansas established an RPS (Renewable Portfolio Standard) mandating utilities acquire 20% of their electricity from renewable energy by 2020 [32]. One of the most prominent renewable energy sources is wind energy. Utility companies now are investing more in wind capture systems to comply with this mandate. This increase in the manufacture of wind turbines has caused researchers to investigate methods to improve the efficiency of captured wind energy and where improvements can be made. This thesis takes a control theory approach to maximizing the power capture of a wind turbine using the concepts of robust estimation, nonlinear control, and Lyapunov-based maximization. A two step control approach to optimize the power capture of a wind turbine is proposed. First, a robust controller is used to estimate unknown aerodynamic properties and regulate the wind turbine tip-speed ratio as it tracks a desired trajectory. Once the tip-speed ratio is regulated within a given tolerance, a Lyapunov-based control approach is developed to provide the robust controller with a desired trajectory to track. This is done by estimating the unknown coefficient of performance of the wind turbine. A discrete update law is then developed to alter the tip-speed ratio and the blade pitch of the wind turbine so that the coefficient of performance is maximized. A simulation is provided of this control strategy and tested under time varying wind conditions and measurement noise in order to demonstrate the controller’s performance. The system simulated is intended to emulate a commercial wind turbine operating in a realistic environment. A detailed discussion of the simulation model, control scheme, and results will be provided to supplement the theoretical controller development, as well as future work for this control application.
Keywords: wind; control; turbine; extremum; lyapunov; engineering; Energy (0791); Engineering, Mechanical (0548)